Analysis of the Need for Interactive E-LKPD Assisted by the Live-Worksheets Platform to Enhance Student Engagement in Reading and Viewing Learning - Rahmayani, Rizka Dwi; Indriyani, Vivi (Language Pedagogy Study Program, Faculty of Languages and Arts, Universitas Negeri Padang, Indonesia, 2024)
This study aims to analyze the development needs of an e-LKPD assisted by the Live-Worksheets platform in reading and viewing lessons at SMA Negeri 2 Padang. The research method used is qualitative descriptive, focusing on the define phase in the 4-D development model. The research subjects consist of teachers and eleventh-grade students, with primary data collected through semi-structured interviews, student learning style questionnaires, and secondary data through documentation study. Data analysis techniques follow Creswell’s (2016) stages: data reduction, data presentation, and data verification. The results show that printed LKPD is still monotonous and lacks interactivity, not supporting the development of students' critical thinking and digital literacy skills. The student learning style questionnaire reveals a variety of preferences that are not fully accommodated by the printed LKPD. Students are more motivated by interactive features, multimedia, and automatic feedback found in the e-LKPD Live-Worksheets. This study also highlights the need for activities that support intensive reading skills and visual analysis, such as evaluating news accuracy and understanding visual elements in media. The integration of e-LKPD Live-Worksheets can enhance learning effectiveness, student engagement, as well as the development of critical thinking and digital literacy skills, taking into account diverse learning styles.